FREEDOM OF EXPRESSION, STRONG LANGUAGE AND PUBLIC SERVANTS - Đajić, Sanja (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
The aim of this contribution is to examine the scope of the freedom of expression of private persons in their encounters with public servants while the latter is on duty. Such situations are bound to happen quite often, sometimes accompanied with intemperance and strong language, so the relevance of the application of human rights to these encounters could potentially be significant. Discussion will be presented against the case-law of the European Court of Human Rights in order to assess whether and to what extent freedom of expression protects against public servants. Given the tendency of the Court to set different scrutiny tests for different categories of expression, and to contextualize expressions and limitations imposed, the ambition of this contribution is to establish whether the Court has distilled a special set of rules for the use of strong language against civil servants while performing public duties. While a regular balancing exercise can include a variety of legitimate interests that potentially can limit freedom of expression, one particular interest will be singled out, that is the right to privacy of public servants and how the balancing of the right to the reputation of public servants with the freedom of expression of private persons can play out.
Keywords: freedom of expression, European Court of Human Rights, Article 10 of the European Convention on Human Rights, civil servants, strong language, insult